Design and experiment of key components for self-propelled harvester for Chinese cabbage - Yongtao Yu; Jiangtao Qi; Yanjun Li; Fuxiang Xie; Jian Song; Yang Bai (Scientific Reports)
Abstract In view of the poor adaptability of the clamping device to different ball diameters and the damage of the pulling device to the bottom of leaf ball in the mechanized harvesting of Chinese cabbage. In order to achieve low-loss and high-efficiency harvesting of Chinese cabbage, a self-propelled Chinese cabbage harvester consisting of clamping conveyor, cutting device and inclined conveyor was designed. Based on the dynamic analysis, the flexible clamping mechanism (maximum clamping force of 152.82 N) and the double disc knife cutting system (rotation speed of 200–400 r min−1) were adopted, combined with the inclined conveyor, to achieve the whole process of clamping-root cutting-conveying integrated operation. Through orthogonal experiments, multi-objective optimization was carried out on key parameters to obtain the better combination of a harvester travel speed of 0.30 m s−1, a clamping and conveying speed of 131 r min−1, and a cutting speed of 339 r min−1. The field validation experiment results showed that the accurate root cutting rate was 94.72% and the damage rate was 5.06%, which satisfied the design and operational performance requirements. The research provides core equipment support for the intensive production of Chinese cabbage, and provides a reference for the mechanized harvesting of knotweed vegetables.